The adoption of remote working practices in the Nigerian banking sector: Are they ready? - Ifeanyi Onyemere; Obinna Alo; Oghenetega Origho; Augustine Okeke (International Journal of Management, Economics and Social Sciences (IJMESS), 2024)
Recently, remote working literature has flourished, but research examining remote working in emerging economies is still lacking, especially within the under-researched context of Africa. Therefore, our paper explored the challenges, benefits, and opportunities of remote working in the Nigerian banking sector and has suggested how to boost the competitiveness and resilience of emerging economies' banking sector. It adopted a qualitative approach involving in-depth semi-structured interviews with 10 bank executives in Nigerian banking sector, and examined their perceptions on remote working, the challenges they face, how these challenges can be minimized, and how the Nigerian banking sector can maximize the benefits of remote working. The findings revealed that our participants are positive about remote working, due to sustainability, increased productivity, economic growth, improved work-life balance, efficiency, and improved workforce motivation. The study also found technological constraints, cybersecurity risks, cultural inertia, supervision challenges, and work-life imbalance as the limitations to these managers' capacity to adopt remote working. The paper highlights how tailored interventions can help to minimize these challenges and contributes to the growing body of remote working and organizational change literature streams.
Keywords: M12; O33; O55; 330; Remote working; Nigeria; banking industry; digitization; deinstitutionalization